Has My Patient Responded?: Interpreting Clinical Measurements such as the Six Minute Walk Test - Dolmage, T.; Hill, Kylie; Evans, R.; Goldstein, R. (Stanford University, 2011)
To correctly interpret clinical measurements it is necessary to understand the standard deviation and the standard error; the former reflects the range or variability of individuals within a sample and the latter reflects the precision for which the group parameters have been estimated. When evaluating an individual patient, test measurement properties such as repeatability will assist in concluding whether a repeated test, measured to monitor the response to an intervention, has changed beyond its natural variability. Using the “best” test has an inherent bias and ignores the natural test variation, whereas the average of repeated tests is more representative of the true value, making it more discriminative to change. Serial measurements to follow progress will increase a clinician's confidence in the observed effects of treatment.